Anchoring ultra-small molybdenum oxide species on covalent triazine frameworks for efficient electrochemical nitrogen fixation. Issue 29 (22nd March 2023) - Lin, Wenwen; Guo, Teng; Zhang, Zihao; Chen, Hao; Lin, Gaobo; Liu, Yifeng; Yao, Siyu; Wang, Liang; Li, Bolong; Wang, Jianghao; Fu, Jie; Ouyang, Pingkai
Abstract : We report a smart ion-exchange strategy to anchor molybdenum oxide particles on charge-modulated conjugated triazine frameworks (Mo/CTF-I) for electrochemically fixing nitrogen. Abstract : We report a smart ion-exchange strategy to anchor molybdenum oxide particles on charge-modulated conjugated triazine frameworks (Mo/CTF-I) for electrochemically fixing nitrogen. The strong interaction between MoO x and CTF-I is conducive to the activation of the inert N2 molecule in the electro-chemical process. As a result, 5% Mo/CTF-I exhibited an excellent faradaic efficiency of 27.3% and an NH3 yield rate of 7.23 μg h −1 mgcat. −1 at −0.405 V vs. RHE in 0.1 M KOH, surpassing most previous reports.